Tuning the properties of redox-active guanidino-functionalized aromatic ligands by substitution: experiment and theory - Peters, Anastasia; Herrmann, Hendrik Hans; Magg, Martin; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2012)
Substitution of the aromatic hydrogen atoms in the electron donors 1,2,4,5-tetrakis(tetramethylguanidino)benzene (1a) and 1,2,4,5-tetrakis(N,N′-dimethyl-N,N′-ethyleneguanidino)benzene (1b) by iodide (to give 2a and 2b) and nitro groups (to give 3a and 3b) afforded new redox-active ligands. Their properties (electron donor capacity, Brønsted basicity and optical spectra) have been analyzed and compared with the unsubstituted 1,2,4,5-tetrakis(guanidino)benzenes. The experimental results are supplemented by quantum chemical calculations. The first late-transition metal complex of the push-pull ligand 3a was prepared and characterized and its oxidation studied.